2014
DOI: 10.1590/0074-0276140384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the WHO classification of dengue disease severity during an epidemic in 2011 in the state of Ceará, Brazil

Abstract: In 2009, the World Health Organization (WHO) issued a new guideline that stratifies dengue-affected patients into severe (SD) and non-severe dengue (NSD) (with or without warning signs). To evaluate the new recommendations, we completed a retrospective cross-sectional study of the dengue haemorrhagic fever (DHF) cases reported during an outbreak in 2011 in northeastern Brazil. We investigated 84 suspected DHF patients, including 45 (53.6%) males and 39 (46.4%) females. The ages of the patients ranged from five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
1
28
0
3
Order By: Relevance
“…It became clear that the improved classification of cases could help the management and treatment of cases in outbreak situations -this study was subsequently published in 2014. 23 Globally published studies In Guayaquil, Ecuador at the Hospital Luis Vernaza, a qualitative study with questionnaires and focus groups has shown that nurses and doctors preferred to use D/SD. Dengue/severe dengue is much easier to apply, practical and didactic, adjusting to the changes in the epidemiological characteristic of the disease -including older populations, including dengue in pregnancy and with comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…It became clear that the improved classification of cases could help the management and treatment of cases in outbreak situations -this study was subsequently published in 2014. 23 Globally published studies In Guayaquil, Ecuador at the Hospital Luis Vernaza, a qualitative study with questionnaires and focus groups has shown that nurses and doctors preferred to use D/SD. Dengue/severe dengue is much easier to apply, practical and didactic, adjusting to the changes in the epidemiological characteristic of the disease -including older populations, including dengue in pregnancy and with comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, of the 121 cases, 106 (87.6%) were not classified as DHF/DSS because the WHO 1997 criteria were not fulfi lled, which indicates the low sensitivity of the WHO 1997 classifi cation for the detection of severe cases (8) (15) (16) (17) (22) and emphasizes the importance of adopting the WHO 2009 classifi cation (10) . Using the WHO 2009 classifi cation, we found that all autopsied individuals in this study could be considered as having SD, suggesting that the WHO 1997 classifi cation is unable to identify severe cases, including those with a high probability of death.…”
Section: Discussionmentioning
confidence: 64%
“…The WHO 2009 classifi cation proposes that countries calculate the fatality from SD by dividing the number of deaths from SD by the population of each region, and then multiplying the obtained value by 1,000. The adoption of the WHO 2009 classifi cation should improve the comparison of dengue fatality rates among different countries because it captures severe cases (8) (15) (22) . It is believed that if this indicator is used, the fatality rates from dengue can be easily compared among different regions, considering population size and the impact of the disease in each region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations